Harnessing AI to Revolutionize Antibiotic Discovery - Sakshi, Sakshi; Adhikary, Arindam; Alam, Inkashaf; Sharma, Kanisheka (Journal of Neonatal Surgery, 2025)
The threats posed by antimicrobial resistance (AMR) being rapidly spread to all parts of the world are undermining the effectiveness of all the available classes of antibiotics and thus a new system of detecting the drug efficiently and effectively is required. The curve of multidrug resistance among pathogenic organisms is increasing at a rate exceeding the paradigms of conventional drug discovery that are both time- and cost-consuming. Over the last few years, the pharmaceutical industry has experienced a paradigm shift, and this is because machine learning (ML) and deep learning (DL) have the capacity to question large chemical libraries, predict antimicrobial activity, and design new antibacterial agents rationally. Modern antibiotics are not only effective in averting existing resistance types, but also in preventing emergence of new resistances. In addition, ML and AI methods are utilized in developing drugs based on infectious disease studies to optimize the representations of compounds using quantitative structure-activity relationship (QSAR) models, optimized descriptors, and neural networks. Deep-learning generative systems and reinforcement-learning systems are also used to design new bioactive molecules to combat resistance mechanisms. Those projects, like BacEffluxPred that categorize efflux pumps that initiate antibiotic resistance, complement genomic surveillance and, at the broader level, define important drug targets. Moreover, machine-learning-based drug discovery platforms combine high-content imaging with classification algorithms to clarify and predict antimicrobial mechanisms of action and in addition to discovering the suboptimally active, which is otherwise undiscoverable. The systems will show a significant improvement compared to the conventional computing resources, decreasing the time required to conduct an experiment and enhancing the reproducibility and efficiency of the results gained in the course of preclinical triage. Altogether, the artificially intelligent methods of antibiotic discovery form a new paradigm with regard to pharmaceutical development and microbiological research. Artificial intelligence has the potential to comprehend current global issues connected with antimicrobial resistance, as the synthesis of anticipatory capability at an expedited reaction and within a profound mechanistic coverage. This highlights how the authors have been determined to combine AI with empirical microbiology in order to develop next generation antibiotics as well as revamp therapeutic innovation